Osteoporosis-related knowledge among Serbian postmenopausal women - Vujasinović Stupar, Nada; Radojčić, Ljiljana; Tadić, Ivana; Pavlov-Dolijanović, Slavica (Vojnosanitetski pregled, 2017)
Background/Aim. Osteoporosis mainly affects women in the early years following menopause. The aim of this study was to determine the level of knowledge about osteoporosis and osteoporosis related risk factors in postmenopausal women in Serbia. Methods. The study included postmenopausal women regardless if suffering from osteoporosis or not. Assessment of knowledge was carried out by using the Osteoporosis Knowledge Assessment Tool - Shorter Version (OKAT-S) questionnaire that was validated for Serbian population. Answers to the 9 questions were coded as 1 –true, or 0 – false or “do not know”. Also, the following risk factors data for osteoporosis were collected: age, the onset and duration of menopause, body mass index (BMI), data on fractures, the incidence of falls, smoking, lifestyle (active, sedentary), regular sunbathing, calcium and vitamin D supplementation, intake of milk and dairy products. Results. A total of 132 postmenopausal women responded to the questionnaire with the response rate of 90.41%. Their knowledge varied from 27.94% to 74.26% of the correct answers, with the average OKAT-S score of 4.5 (SD = 2.55), which was 50% of the maximum possible score. Only 2 participants (1.47%) filled the all OKAT-S items correctly, while 11 (8.09%) of them did not have the proper answer to any question. A reduced bone density (T-score below -1) was registered in 40.91% of the women, previous fractures in 49 (34.51%), and more or less 3 falls registered in 9.59% or 4.79%, respectively. Conclusion. The Serbian version of the questionnaire OKAT-S revealed generally poor knowledge on osteoporosis among postmenopausal women in Serbia. Developing effective interventions and public health programms could be helpful in general education towards understanding osteoporosis and risk factors. Promotion of preventive measures and healthy behaviour may prevent or at least slow down the accelerated bone loss in postmenopausal women.
Keywords: osteoporosis; postmenopausal; risk factors; knowledge; attitude to health; serbia